State Policy in Social Security of War Invalids during Great Patriotic War (by Example of Vladikavkaz) - L. C. Khabliyeva; Z. V. Sosranova (Научный диалог)
The directions of activity of authorities and the state on social security of invalids of war during the Great Patriotic war are analyzed. The authors note that the multiple increase in the number of disabled people since the beginning of the Great Patriotic war led to a change in the system of social security and rehabilitation of disabled people. It is reported that over the years there has been an increase in state assistance, which included, in addition to the appointment of pensions and benefits, provision of food and industrial goods, preferential provision of housing, land, fuel. It is emphasized that the state takes additional measures aimed at training and further employment of war invalids. Provides information that in conditions of wartime rationing disabled veterans receive food aid. The financial security of disabled veterans, the supply of food and necessities is discussed. The article raises the question of the structure of state support bodies to assist disabled people of the Great Patriotic war. The authors argue that, in general, social security for persons with disabilities during the war years became systemic, but the amount of payments remained low and did not compensate for the lost earnings, which led to the need for the introduction of natural forms of support and additional benefits.